A paper-based fluorescent test paper and its preparation method and application

The modified polyacrylonitrile nanofiber film was prepared and modified by electrospinning, and metal organic gels were grown in situ, and paper-based fluorescent test strips with blue fluorescence properties were prepared, which solved the problem of difficulty in detecting doxycycline contaminants in the environment in the prior art, and achieved efficient and quantitative detection effects.

CN116240726BInactive Publication Date: 2025-04-22ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211090228.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-07
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to detect doxycycline contaminants in the environment quickly, at low cost, quantitatively visually, and the processability of metal-organogel materials is insufficient.

Method used

Polyacrylonitrile nanofiber films were prepared by electrospinning, and metal organic gel (Zr-MOG) was grown in situ on the nanofiber surface by modification modification and hydrothermal-solvent thermal method to prepare paper-based fluorescent test strips with blue fluorescence properties.

Benefits of technology

A rapid quantitative visual detection of doxycycline was achieved, with the detection limit as low as 787.5 ppb, and the fluorescent test strips had excellent fluorescence response performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116240726B_ABST
    Figure CN116240726B_ABST
Patent Text Reader

Abstract

The invention discloses a paper-based fluorescent test paper and a preparation method and application thereof, wherein PAN NFM is activated by carbodiimide and succinimide, and then 6-aminocaproic acid and electrospun PAN NFM are chemically grafted and modified under mild conditions at room temperature, and Zr-MOG is further in situ grown on the surface of the modified 6-ACA-PAN NFM under mild reaction conditions to obtain a test paper with excellent blue fluorescence performance. In actual detection, the fluorescence response of the fluorescent test paper Zr-MOG@6-ACA-PAN NFM to DOX is quickly completed within 10 seconds, and the visual detection limit is as low as 787.5ppb.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of analytical chemistry and specifically relates to a paper-based fluorescent test paper and a preparation method and application thereof, through which a metal organic gel @ polyacrylonitrile nanofiber (Zr-MOG@6-ACA-PAN NFM) fluorescent test paper can be prepared under simple and mild reaction conditions, and the test paper can have excellent fluorescence response performance and can be used for visual detection of doxycycline pollutants in the environment. Background Art

[0002] Up to 92% of patients have used antibiotic-antiviral drug combination therapy, among which antibiotics such as doxycycline (DOX), azithromycin, and amoxicillin can effectively block the inflammatory storm and are widely used to improve lung infections and reduce mortality. However, the abuse of antibiotics such as DOX brings additional burdens to the environment, and antibiotic resistance is a problem that may affect the lives of millions of people in the next few decades. Therefore, how to quickly and quantitatively visualize the detection of antibiotics at low cost has extraordinary significance and broad commercial prospects for human health. Therefore, we are looking for simple detection methods and cheap equipment to meet a large number of analytical testing needs, and low-cost paper-based test strips are an ideal solution. Its advantages are portability, low cost, good specificity, and can achieve the detection of target pollutants.

[0003] At the same time, in recent years, great progress has been made in the use of metal organic gels (MOG) as luminescent sensing materials due to their unique short response time and remarkable luminescent properties. However, a prominent obstacle to the use of metal organic materials in the industry is their low processability, because the materials usually exist in the form of insoluble, brittle, crystalline powders. In order to address the shortcomings of such materials such as MOF and MOG, a hybridization strategy with organic polymers prepared by electrospinning can be used to obtain a composite material that has both the excellent chemical properties of metal organic materials-polymers and the high processability of organic polymers. The resulting material can be conveniently used as a fluorescent test paper. Summary of the invention

[0004] In view of the shortcomings of the existing technical problems, the technical problem to be solved by the present invention is to provide a preparation method of a metal organic gel nanofiber film (Zr-MOG@6-ACA-PAN NFM) and its application, and to prepare a method for modifying PAN NFM prepared by electrospinning to help Zr-MOG grow uniformly in situ, so as to obtain a test paper with blue fluorescence performance, which can quickly and quantitatively visualize and specifically detect doxycycline pollutants in the environment.

[0005] The present invention adopts the following technical solutions:

[0006] A method for preparing a paper-based fluorescent test paper, which comprises activating PANNFM by using carbodiimide EDC and succinimide NHS, then chemically grafting 6-aminocaproic acid 6-ACA with electrospun PAN NFM under mild conditions at room temperature, and further in-situ growing Zr-MOG on the surface of the modified 6-ACA-PAN NFM under mild reaction conditions to obtain a test paper with blue fluorescent properties.

[0007] The preparation method comprises the following steps:

[0008] (1): Preparation of polyacrylonitrile nanofiber film: 1.3 g to 2.6 g of polyacrylonitrile (PAN) powder was dissolved in 10 ml to 20 ml of N, N-dimethylformamide (DMF), and vigorously stirred at room temperature for 3 hours to fully dissolve the PAN powder to obtain a clear and transparent ready-to-use electrospinning solution, and the polyacrylonitrile nanofiber film was prepared by electrospinning;

[0009] (2): Modification of the film, soak 0.3-0.6g of rectangular sheet PAN nanofiber membrane in NaOH alkaline solution for 2h; take out the nanofiber membrane, rinse with deionized water until neutral, then transfer to EDC aqueous solution for further modification, shake on a shaker for 20-30 minutes, and then add NHS powder; the mass ratio of the three substances is PAN:EDC:NHS=1:3:4; shake the reaction solution at room temperature for 12-24 hours to complete the activation process; then take out the activated membrane and rinse with deionized water for 5-20 minutes, then place the modified activated EDC / NHS-PAN NFM in 200-400mL of 0.22M 6-ACA modified aqueous solution for 24 hours to continue grafting, and the reaction temperature is controlled at 35°C; after completing the above steps, rinse with deionized water twice and dry to obtain the modified 6-ACA-PAN NFM;

[0010] (3): In situ growth of Zr-MOG, 0.58g~0.116g ZrCl4, 1.02g~2.10g 5-AIA and 1.05g~2.04g 1,3,5-benzenetricarboxylic acid (BTC) were ultrasonically treated in a mixed solution of 80mL DMF and 20mL H2O for 0.5-1h to obtain a light yellow clear solution; then 10-20 rectangular modified 6-ACA-PAN NFM films were immersed in the above clear solution and ultrasonically treated for 15-30 minutes to allow the reacted stock solution to be fully diffused and distributed between the nanofibers; then the mixed system of the membrane and the solution was transferred to a forced air drying oven and heated at 90℃ for 10-24h; after the reaction was completed, the prepared Zr-MOG@6-ACA-PAN NFM was taken out, washed with deionized water, and vacuum dried at room temperature to obtain Zr-MOG@6-ACA-PAN NFM thin film fluorescent test paper.

[0011] In the preparation method, in step (1), the electrospinning is: under the conditions of a working environment temperature and a relative humidity of 20±2°C and 40±10°C, respectively, the PAN solution is electrospun at a fixed speed of 5 mL / h and a working voltage of 40 to 50 kV; in addition, the collection distance from the electrospinning nozzle head to the non-woven fabric receiver is maintained at 150 to 200 mm.

[0012] In the preparation method, in step (2), the NaOH alkaline solution is prepared by dissolving 6.0-8.0 g of NaOH in 100 mL of deionized water and vigorously stirring at 55° C. until the solution is completely dissolved to obtain an alkaline solution.

[0013] The preparation method, in step (2), is then transferred to 200 ml of EDC aqueous solution for further modification.

[0014] A paper-based fluorescent test paper obtained according to any of the preparation methods.

[0015] The paper-based fluorescent test paper is used in the visual detection of doxycycline pollutants in the environment.

[0016] The present invention has the following advantages:

[0017] (1) PAN NFM was activated by carbodiimide and succinimide, and then 6-aminocaproic acid was chemically grafted with electrospun PAN NFM under mild conditions at room temperature. Subsequently, Zr-MOG was in situ grown on the modified 6-ACA-PAN NFM surface under mild reaction conditions to obtain a test paper with excellent blue fluorescence performance. In actual detection, the fluorescence response of the fluorescent test paper Zr-MOG@6-ACA-PAN NFM to DOX was completed quickly within 10 seconds, and the visual detection limit was as low as 787.5 ppb.

[0018] (2) The method and ideas provided by the present invention use a strategy combining electrospinning, modification, and hydrothermal-solvothermal growth to prepare Zr-MOG@6-ACA-PAN NFM thin film fluorescent test paper. Compared with most current MOG fluorescence detection studies that are still focused on powder crystals and solution states, the thin film paper-based sensor can be used as a portable fluorescent test paper, which is convenient for daily visual detection and has the advantages of being more convenient and efficient than fluorescence sensing in powders and solutions.

[0019] (3) The modification method provided by the present invention overcomes the weak interaction between MOG and polymer, solves the disadvantage that Zr-MOG is difficult to grow in situ on polymer nanofibers, and the modification process provides abundant active sites for MOG growth. The nanofiber membrane has the advantages of good hydrophilicity and high fluorescence stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : SEM morphological image of unmodified PAN NFM prepared by electrospinning in Example 1;

[0021] Figure 2 : SEM morphological image of the modified 6-ACA-PAN NFM prepared in Example 2;

[0022] Figure 3 : SEM morphology image of Zr-MOG@6-ACA-PAN NFM prepared in Example 3;

[0023] Figure 4 : TEM internal image of 6-ACA-PAN NFM prepared in Example 2;

[0024] Figure 5 : TEM internal image of Zr-MOG@6-ACA-PAN NFM prepared in Example 3;

[0025] Figure 6 : XRD crystal structure characterization of Zr-MOG@6-ACA-PAN NFM prepared in Example 3;

[0026] Figure 7 : FTIR functional group structure characterization of Zr-MOG@6-ACA-PAN NFM prepared in Example 3;

[0027] Figure 8 : Fluorescence spectra of the Zr-MOG@6-ACA-PAN NFM prepared in Example 4 with different concentrations of DOX (0-200uM) added and a series of fluorescence images under 360nm UV light;

[0028] Fig. 9 :Flowchart of detecting DOX using Zr-MOG@6-ACA-PAN NFM prepared in Example 4;

[0029] Fig.10 : CIE coordinate diagram of Zr-MOG@6-ACA-PAN NFM prepared in Example 4 (a) and the linear relationship between R / B value and DOX concentration in the range of 0-200uM (b);

[0030] Fig.11 : The selectivity of Zr-MOG@6-ACA-PAN NFM prepared in Example 4 to different types of antibiotics, and its anti-interference in the presence of different types of antibiotics; DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with specific embodiments.

[0032] The present invention provides a synthetic method for assisting the in-situ growth of Zr-MOG by modifying PAN NFM prepared by electrospinning, using 6-aminocaproic acid and PAN NFM for grafting reaction, providing a large number of coordination active sites on the surface of nanofibers, providing coordination space and conditions for the in-situ growth of Zr-MOG, and then preparing in-situ grown Zr-MOG@6-ACA-PAN NFM film by hydrothermal-solvothermal method. The technical problem to be solved by the present invention is to provide a preparation method of a metal organic gel nanofiber film (Zr-MOG@6-ACA-PAN NFM) composite material and its application in visual detection of doxycycline (DOX), comprising the following steps:

[0033] Embodiment 1:

[0034] Preparation of PAN NFM thin films by electrospinning

[0035] 2.0 g of high polymer polyacrylonitrile (PAN) molecules were dissolved in an organic solvent to prepare an electrospinning solution, and stirred at room temperature for 3 h to fully dissolve it to obtain a solution to be electrospun; the prepared solution to be electrospun was electrospun to obtain an unmodified PAN nanofiber film, which was dried at room temperature for standby use; Figure 1 Shown is the SEM morphology image of the unmodified PAN NFM prepared by electrospinning in Example 1;

[0036] Example 2: Grafting modification of PAN NFM

[0037] (1) Preparation of modification solution: 7.0 g NaOH was dissolved in 100 mL deionized water and stirred vigorously at 55 °C until completely dissolved. At the same time, 0.3 g (about 10 pieces, each piece weighing 0.03 g) of rectangular PAN nanofiber membrane was soaked in the above alkaline solution for 2 h. Then, the film was taken out, rinsed with deionized water until neutral, and then transferred to 200 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) aqueous solution (containing 3.048 g EDC) for further modification. It was placed on a shaker for 20 minutes, and then N-hydroxysuccinimide (NHS) (containing 2.603 g NHS) aqueous solution was added. The mass ratio of the three substances was PAN:EDC:NHS=1:3:4. The reaction solution was shaken at room temperature for 12 hours to complete the activation process. Then, the activated membrane was taken out and rinsed with deionized water for 5 minutes, and then the modified and activated polymer nanofiber membrane EDC / NHS-PAN NFM was placed in 200 mL of 0.22 M 6-aminohexanoic acid (6-ACA) modified aqueous solution for 24 hours to continue grafting, and the reaction temperature was controlled at 35 °C;

[0038] (3) taking out the modified polymer nanofiber film from the beaker, washing it with deionized water until the pH of the wet film reaches neutral, and then drying it at room temperature to obtain a successfully modified polymer nanofiber film to be used for the in-situ growth of Zr-MOG; Figure 2 and Figure 4 The fibers shown exhibit a relatively smooth surface.

[0039] Example 3: In-situ growth of Zr-MOG to prepare fluorescent test paper Zr-MOG@6-ACA-PAN NFM

[0040] 0.58 g of ZrCl4, 1.05 g of 1,3,5-benzenetricarboxylic acid (1,3,5-BTC), and 1.02 g of 5-aminoisophthalic acid (5-AIA) powder were weighed respectively in a mixed solution of 80 mL of N,N-dimethylformamide (DMF) and 20 mL of water, and ultrasonicated until completely dispersed, and then 0.3 g (about 10 pieces, each piece weighing 0.03 g) of the modified polymer nanofiber film prepared in Example 2 was added, and then placed together in a polytetrafluoroethylene liner, and in-situ grown at 90 ° C for 10 h to obtain Zr-MOG@6-ACA-PAN NFM, washed with deionized water for 30 minutes to remove the residual solution, and dried at room temperature for visual detection;

[0041] like Figure 3 , 5 , 6 and Figure 7 The rough bark-like surface of the fibers shown indicates that the MOG particles have grown effectively. At the same time, the XRD and FTIR characterization methods observed the diffraction peak related to MOG at 11° and the characteristic peaks related to the stretching vibration and in-plane bending vibration of the Zr-O skeleton at 657cm-1, 759cm-1 and 1380cm-1, which further proved the existence of MOG.

[0042] Example 4: Visualization of specific recognition of doxycycline by Zr-MOG@6-ACA-PAN NFM fluorescent test paper

[0043] (1) Visual detection experiment of DOX by fluorescent test paper: 0-200 nM aqueous solution of doxycycline (DOX) was added to the prepared Zr-MOG@6-ACA-PAN NFM fluorescent nanofiber membrane, and the blue fluorescence of Zr-MOG@6-ACA-PANNFM was observed to be quenched. The visual changes of the luminescence of the fluorescent test paper were read out through the color recognition APP installed in the smartphone to obtain a series of concentration-dependent fluorescence images of red, green and blue light (RGB) changes. As the concentration of DOX increased, the degree of quenching gradually changed, so that DOX could be quickly and quantitatively detected visually; Figure 8 , 9and Fig.10 It was shown that the electrospinning-based modified nanofiber fluorescent test strips can quickly and quantitatively monitor DOX contaminants by reading RGB visualization results.

[0044] (2) Experiment on selectivity and interference performance of fluorescent test paper: By adding other antibiotics (10 -2 M) A selectivity experiment was performed similarly, and the emission spectrum intensity was recorded by a fluorescence spectrophotometer. The fluorescent test paper showed an obvious fluorescence quenching reaction to DOX, while the fluorescence changes caused by other antibiotics were weak.

[0045] In the interference experiment, other antibiotics (10M -2 ) were mixed with DOX solution (5×10 -3 M), drop the mixed antibiotic solution on the test paper, and measure the emission spectrum and RGB color change of the test paper. Fig.11 As shown (blue top: interference test in the presence of other target antibiotics; pink bottom: comparison of quenching of selectivity test of different antibiotics), other antibiotics and drugs have little effect on the fluorescence emission of Zr-MOG@6-ACA-PAN NFM.

[0046] Various antibiotics include: such as macrolides (azithromycin, AZM; roxithromycin, ROX), β-lactams (amoxicillin, ACL; ceftazidime, CAZ), lincomycin (lincomycin, LCC), chloramphenicol (thiamphenicol, THI; chloramphenicol, CHL), nitroimidazoles (metronidazole, MDZ; tinidazole, TDZ), nitrofurans (nitrofurantoin, NFT; nitrofurazone, NFZ), aminoglycosides ( Streptomycin, SM; kanamycin, KNM; gentamicin, GTM), tetracycline (doxycycline, DOX), peptides (vancomycin, VCC), sulfonamides (sulfamethoxazole, SDM; sulfamethoxazole, SMZ; sulfathiazole, ST) and some antiviral drugs for influenza and respiratory diseases, such as (acetaminophen, APAP; hydroxychloroquine, HCQ; ribavirin, RBV; teicoplanin, TEC; oseltamivir, OTV).

[0047] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method for preparing a paper-based fluorescent test paper, characterized in that: PAN NFM is activated by carbodiimide EDC and succinimide NHS, and then 6-aminocaproic acid 6-ACA is chemically grafted with electrospun PAN NFM under mild conditions at room temperature, and Zr-MOG is further in situ grown on the modified 6-ACA-PAN NFM surface under mild reaction conditions to obtain a test paper with blue fluorescence performance; the process comprises the following steps: (1): Preparation of polyacrylonitrile nanofiber film: 1.3 g~2.6 g polyacrylonitrile PAN powder was dissolved in 10 ml~20 ml N,N-dimethylformamide DMF, and stirred vigorously at room temperature for 3 hours to fully dissolve it, to obtain a clear and transparent ready-to-use electrospinning solution, and the polyacrylonitrile nanofiber film was prepared by electrospinning; (2): Modification of the film: soak 0.3-0.6 g rectangular sheet of PAN nanofiber membrane in NaOH alkaline solution for 2 h; take out the nanofiber membrane, rinse it with deionized water until neutral, then transfer it to EDC aqueous solution for further modification, shake it on a shaker for 20-30 minutes, and then add NHS powder; the mass ratio of the three substances is PAN:EDC:NHS=1:3:4; shake the reaction solution at room temperature for 12-24 hours to complete the activation process; then take out the activated membrane and rinse it with deionized water for 5-20 minutes, then place the modified and activated EDC / NHS-PAN NFM in 200-400 mL of 0.22M 6-ACA modified aqueous solution for 24 hours to continue grafting, and the reaction temperature is controlled at 35°C; after completing the above steps, rinse it twice with deionized water and dry it to obtain the modified 6-ACA-PAN NFM; (3): In situ growth of Zr-MOG, 0.58g~0.116g ZrCl4, 1.02g~2.10g 5-AIA and 1.05g~2.04g 1,3,5-benzenetricarboxylic acid were ultrasonically treated in a mixed solution of 80 mL DMF and 20 mL H2O for 0.5-1 h to obtain a light yellow clear solution; then 10-20 rectangular modified 6-ACA-PAN NFM films were immersed in the above clear solution and ultrasonically treated for 15-30 minutes to allow the reacted stock solution to be fully diffused and distributed between the nanofibers; then the mixed system of the membrane and the solution was transferred to a forced air drying oven and heated at 90°C for 10-24 h; after the reaction was completed, the prepared Zr-MOG@6-ACA-PAN NFM was taken out, washed with deionized water, and vacuum dried at room temperature to obtain Zr-MOG@6-ACA-PAN NFM thin film fluorescent test paper.

2. The preparation method according to claim 1, characterized in that: In step (1), the electrospinning is as follows: under the working environment temperature and relative humidity of 20±2°C and 40±10°C, the PAN solution is electrospun at a fixed speed of 5 mL / h and a working voltage of 40~50 kV; in addition, the collection distance from the electrospinning nozzle head to the non-woven fabric receiver is maintained at 150~200 mm.

3. The preparation method according to claim 1, characterized in that: In step (2), the NaOH alkaline solution is prepared by dissolving 6.0-8.0 g of NaOH in 100 mL of deionized water and vigorously stirring at 55° C. until the solution is completely dissolved to obtain an alkaline solution.

4. The preparation method according to claim 1, characterized in that: In step (2), the mixture was then transferred to 200 ml of EDC aqueous solution for further modification.

5. A paper-based fluorescent test paper obtained according to any one of claims 1 to 4.

6. Use of the paper-based fluorescent test paper according to claim 5 in the visual detection of doxycycline pollutants in the environment.